Overspending driven by oversized single dose vials of cancer drugs. (29th February 2016) - Bach, Peter B; Conti, Rena M; Muller, Raymond J; Schnorr, Geoffrey C; Saltz, Leonard B
Abstract : Peter B Bach and colleagues call for an end to contradictory regulatory standards in the US that allow drug manufacturers to boost profits by producing single dose vials containing quantities that increase leftover drug